Determination of phenolic contents of red chilli (Capsicum Annuum) and paddy chilli (Capsicum Frutescens) for pest resistance observation - Siti Norma Azizan (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Agriculture is one of the back bones of Malaysian economics. Nowadays, this field is widely involved in research and development to increase the quality and production of food supply. This research focuses on chilli, a vegetable crop of high cash value. Unfortunately, it is highly infested by plant-sucking insects that also transmit several viruses. Two types of widely consumed chillies are Red Chilli (Capsicum annuum) and Paddy Chilli (Capsicum frutescens). Phenolic content is one of the secondary metabolites that give resistance characteristic to the plant for disease and the present research compares the total phenolic contents in these two varieties using extracts from different parts of the plant. Roughly, the C. annuum easily infected by viruses and diseases compared to C. frutescens.. UV-Vis device was used and the absorbance of samples tested was calculated to get the concentration of Gallic Acid (phenolic). From the results obtained, the maximum concentration of phenolic were found in the stem of C. frutescens with concentration 415mg/L compared to others part and the C. frutescens also recorded the plant that has highest value of phenolic concentration compared to C annuum.